Measurement of High Numerical Aperture Cylindrical Surface with Iterative Stitching Algorithm - Dingfu Chen; Junzheng Peng; Sergiy Valyukh; Anand Asundi; Yingjie Yu (Applied Sciences, 2018)
There are some limitations in null test measurements in stitching interferometry. In order to meet the null test conditions, the moving distance between the sub-apertures often deviates from the theoretical preset distance, which leads to a position deviation of sub-apertures when measured. To overcome this problem, an algorithm for data processing is proposed in this paper. An optimal estimation of the deviation between sub-apertures is used to update their positions, and then a new overlapped region is obtained and again optimized. This process is repeated until the algorithm converges to an acceptable tolerance, and finally exact stitching is realized. A cylindrical lens was taken as an object for experimental examination of the proposed method. The obtained results demonstrate the validity, reliability, and feasibility of our iterative stitching algorithm.